A systematic approach for assessing spatially and temporally differentiated opportunity costs of biodiversity conservation measures in grasslands - Melanie Mewes; Martin Drechsler; Karin Johst; Astrid Sturm; Frank Wätzold (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
Biodiversity loss in Europe is caused to a large extent by agricultural intensification. To halt this loss and to support species and habitat types in agricultural areas, agri-environment schemes have been introduced in Europe to compensate farmers for (costly) conservation measures. Currently, agri-environment schemes for grassland in general consider only a few conservation measures with fixed dates and a payment for average opportunity costs, e.g. for later mowing. A systematic approach that calculates farmers' opportunity costs in relation to the timing of grassland use is still lacking. We fill this gap by developing a systematic agri-economic cost assessment approach. Our approach is general enough to be applicable on a large spatial scale but can still sensitively differentiate among different timings. Moreover it is straightforward and time-saving enough to be suitable for implementation in regional scale optimisation procedures. We demonstrate this by applying the systematic cost assessment in the decision support software DSS-Ecopay using the example of grassland species and habitats conservation in the German federal state of Saxony.
Keywords: 330; biodiversity conservation; cost-effectiveness; ecological-economic modelling; agri-environment scheme; grassland; DSS-Ecopay